Exposure to blue light reduces antimicrobial resistant Pseudomonas aeruginosa isolated from dog ear infections - Gigante, Adriano M.; Hadis, Mohammad A.; Secker, Bailey; Shaw, Stephen C.; Cooper, Paul R.; Palin, William M.; Milward, Michael R.; Atterbury, Robert J. (Frontiers in Microbiology, 2024)
Pseudomonas aeruginosa is a leading cause of canine otitis externa. Enrofloxacin is often applied topically to treat this condition, although recalcitrant and recurring infections are common. There is evidence that exposure to blue light (400 to 470 nm) has a bactericidal effect on P. aeruginosa. In the present study, we determined the biocidal effect of blue light (375 to 450 nm), alone or in combination with enrofloxacin, against six strains of P. aeruginosa from dogs with otitis externa (five of which were resistant to enrofloxacin). Treatment of planktonic cell cultures with blue light resulted in significant (p<0.5) reductions in CFU counts, in some cases below the limit of detection. The greatest bactericidal effect followed exposure to light at 405 nm wavelength (p<0.05). Exposure to blue light for 20 min usually resulted in a greater CFU reduction than enrofloxacin treatment, and combination treatment typically resulted in the largest reductions. Genome analysis of the P. aeruginosa strains established that enrofloxacin resistance was likely the result of a S466F substitution in GyrB. However, there was no clear association between genotype and susceptibility to blue light treatment. For the first time, these results suggest that blue light treatment, particularly at 405 nm wavelength, and especially in combination with enrofloxacin therapy, could be an effective treatment for otherwise recalcitrant canine otitis externa caused by P. aeruginosa. This may also provide a way of extending the usefulness of enrofloxacin therapy which would otherwise be ineffective as a sole therapeutic agent.